1981
DOI: 10.1111/j.1365-3083.1981.tb00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Structural and Antigenic Studies of Light‐chain Amyloid Proteins

Abstract: The major subunit protein of amyloid fibrils (758) isolated from a patient with systemic amyloidosis and studied by N-terminal amino acid sequence analysis was found to be almost identical to the sequence of a V lambda IV Bence-Jones protein and a previously described A lambda IV amyloid protein. The two A lambda IV amyloid proteins showed strong antigenic cross-reaction, appearing as antigenic identity in double immunodiffusion tests using anti-A lambda IV antiserum raised against one or the other of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Proteins SUT, GIO, MOR, WAN, AND WIN had amino acid residues within the FRI characteristic for proteins of the VAv, subgroup. Each of the proteins was homologous in sequence and closely resembled the sequences of the prototype XVI proteins AR, JAM, and YAM-L (4) and of the XVI proteins KIN-L (12), NIG-48 (13) and RS (14). The sequence of the first 6 residues of X-chain BUC (data not shown) was also consonant with that of a XVI protein.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Proteins SUT, GIO, MOR, WAN, AND WIN had amino acid residues within the FRI characteristic for proteins of the VAv, subgroup. Each of the proteins was homologous in sequence and closely resembled the sequences of the prototype XVI proteins AR, JAM, and YAM-L (4) and of the XVI proteins KIN-L (12), NIG-48 (13) and RS (14). The sequence of the first 6 residues of X-chain BUC (data not shown) was also consonant with that of a XVI protein.…”
mentioning
confidence: 60%
“…Four additional XVI proteins have since been identified from sequence analyses of the light chains isolated from the IgAX protein YAM (11), the IgGX protein KIN (12), the Bence Jones protein NIG-48 (13), and the protein isolated from amyloid fibrils of patient RS (14). Variable region subgroups of human K-and X-light chains have been also identified immunochemically (3,16 V region antigenic determinants when tested with antisera prepared against the alkali-denatured protein AR (14). We found that an antiserum prepared against the X-Bence Jones protein SUT from a patient with myeloma-associated amyloidosis had unique specificity for antigenic determinants associated with the V region of XVI light chains.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases the amino acid sequences of the fibril and the monoclonal urine or serum protein have been determined and found to be identical (3,4). Many fibril proteins have been studied in detail and reported (3)(4)(5)(6)(7)(8)(9)(10). In only 5 of 17 cases have the deposits contained intact L-chains.…”
Section: Introductionmentioning
confidence: 99%
“…6 The fibrils are organized as rigid, non-branching rods which orient with a slight twist longitudinally. They are of indeterminate length, but consistently 75-100 A in diameter.7 Each fibril appears to contain two or more filamentous subunits (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) A diameter). This distinct ultrastructure of the fibrils has been reported in all types of amyloid, both of human and animal origin?…”
mentioning
confidence: 99%